BIO-CONCRETE as Advanced and Sustainable Concrete - Abdullah Faisal Abdul Aziz; Mohd Irwan Juki; Norzila Othman (Penerbit UTHM, 2022)
High-performance concrete is frequently used in construction practice, not only because of its high-strength qualities, but also because of its high resistance to other external influences. Therefore, many studies have been performed to improve concrete properties. There are various methods for improving concrete properties, and one of them is by employing bacteria in concrete. Bacteria play an important role in bio-concrete by promoting deterioration in porous materials, improving sand properties, sealing the concrete porosity, and enhancing the durability of building materials. Mineral precipitation that results from metabolic activities of some microorganisms has emerged as a new research area for construction materials to improve the overall properties of concrete. These bacteria can precipitate calcium carbonate (CaCO3) by the production of urease enzyme. The precipitation of calcium carbonate crystals occurs by heterogeneous nucleation on bacteria cell walls. Super-induced CaCO3 precipitation has been proposed as an alternative and environmentally friendly crack repair technique. Microbial carbonate precipitation decreases the permeation properties of the concrete. Hence, a deposition of a CaCO3 layer on the surface of bacteria in concrete results in decreased water absorption and porosity. In addition, bio-concrete technology represents one of the biological CO2 sequestration applications specially in bio-foamed concrete, which has high level of pores. Acceleration of carbonation process under extreme pH and anaerobic condition of bio-concrete takes place due to the bacterial enzymes reaction carbonic anhydrase (CA) and urease which acts to precipitate CaCO3 into concrete pores.